Analisis Dampak Financial Distress Terhadap Hubungan Antara Pengungkapan Laporan Keberlanjutan Dan Konservatisme - Hanan Octiana; Anita Nopiyanti; Andi Manggala Putra (Institut Bisnis dan Informatika Kesatuan, 2020)
This research is a quantitative study that aims to determine the influence of the impact of financial distress moderate relationship between sustainability reports on conservatism. Which is measured using the method with the amount of time required. Financial distress as measured by modified zscore, sustainability report measured by sustainability report index GRI G4, conservatism as measured by market to book ratio. The population used in this study is a manufacturing company in The Sub Consumer Good Industry Sector,which is listed on the Indonesia Stock Exchange (IDX) in 2016-2018. The sample used was 40 manufacturing companies in The Sub Consumer Good Industry Sector listed on the Indonesia Stock Exchange and the official website of each company in the 2016-2018 period, which selected the use of the non-probability method as a method. The study tested the hypothesis using Multi Linear Regression analysis with the STATA 13 program and there was a signification level 0.5 or 5%. The results of examination are obtained (1) there is no significant effect of sustainability reports on conservatism, (2) there is no effect of financial distress moderating the relationship between sustainability reports and conservatism. Keywords: financial distress, sustainability report, and conservatism